From perception to inference: Utilization of probabilities as decision weights in children - Betsch, Tilmann (Mem Cognit, 2021)
In a probabilistic inference task (three probabilistic cues predict outcomes for two options), we examined decisions from 233 children (5–6 vs. 9–10 years). Contiguity (low vs. high; i.e., position of probabilistic information far vs. close to options) and demand for selectivity (low vs. high; i.e., showing predictions of desired vs. desired and undesired outcomes) were varied as configural aspects of the presentation format. Probability utilization was measured by the frequency of following the predictions of the highest validity cue in choice. High contiguity and low demand for selectivity strongly and moderately increased probability utilization, respectively. Children are influenced by presentation format when using probabilities as decision weights. They benefit from perception-like presentations that present probabilities and options as compounds. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.3758/s13421-020-01127-0.